Mindful language learning: The effects of college students' mindfulness on short-term vocabulary retention. (November 2022) - Zeilhofer, Luisa; Sasao, Yosuke
Abstract: Educators are increasingly implementing holistic approaches into the foreign language classroom, with one popular method being mindfulness. Mindfulness has been associated with better grades and well-being in higher education. However, no study has yet explored the language-specific relationship between mindfulness and second language acquisition (SLA). This study investigated the relationship between the mindfulness level of 269 Japanese undergraduates and their ability to learn new L3 words in German. The study further examined the extent to which different domains of mindfulness were related to the ability to learn new vocabulary, as well as the relationship between mindfulness and the different vocabulary test parts (receptive, productive, grammatical gender). Correlation and multiple regression analyses revealed that higher mindfulness was associated with better vocabulary retention. In particular, the mindfulness dimension "Acting with Awareness" was key for all connections. Notably, the L1 and L3 parts showed a different relationship with different mindfulness dimensions: "Non-judging" was crucial for the productive part and "Observing" was decisive for the receptive part. These findings indicate that mindfulness not only improves general academic performance, but also has a direct relationship with SLA. Finally, this suggests that mindfulness training for students may be a novel approach to facilitate vocabulary learning. Highlights: Mindfulness may be linked to better short-term vocabulary retention. 269 undergraduate students from a Japanese university participated. The mindfulness domains of "Acting with awareness" and "Observing" are the key factors. The receptive and the productive part show a different relationship with different domains. Mindfulness exercises can be helpful for vocabulary learning.